2024
DOI: 10.3390/w16030431
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Isolated Rhodococcus sp. S2 from Landfill Leachate Capable of Heterotrophic Nitrification and Aerobic Denitrification

Xianglan Chen,
Shuangfei Li,
Wenxuan Zhang
et al.

Abstract: Nitrogen removal through heterotrophic nitrification–aerobic denitrification (HN–AD) has been acknowledged as one of the most efficient and cost-effective nitrogen removal processes. This study involved the isolation of a novel HN–AD bacterium (Rhodococcus sp. S2) from landfill leachate. Rhodococcus sp. S2 exhibited high nitrogen removal performance under aerobic conditions without the accumulation of nitrite as an intermediate. The maximum removal efficiencies for NH4+-N, NO2−-N, and NO3−-N were found to be 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…From the fitting results, it could be seen that strain JQ1004 had an obvious delay period in degrading nitrogen pollutants, which was 5.91 h or 12.74 h, respectively, for metabolizing ammonia or nitrate. These results indicated that the strain JQ1004 showed a preference for degrading ammonia, which was in accordance with previously published work [23]. When using different nitrogen sources, the average degradation rate of ammonia was significantly higher than that of nitrate based on the kinetic parameters.…”
Section: Kinetic Analysis Of Nitrogen Degradation and Cell Growthsupporting
confidence: 92%
“…From the fitting results, it could be seen that strain JQ1004 had an obvious delay period in degrading nitrogen pollutants, which was 5.91 h or 12.74 h, respectively, for metabolizing ammonia or nitrate. These results indicated that the strain JQ1004 showed a preference for degrading ammonia, which was in accordance with previously published work [23]. When using different nitrogen sources, the average degradation rate of ammonia was significantly higher than that of nitrate based on the kinetic parameters.…”
Section: Kinetic Analysis Of Nitrogen Degradation and Cell Growthsupporting
confidence: 92%